2018
DOI: 10.3389/fevo.2018.00210
|View full text |Cite
|
Sign up to set email alerts
|

Wild Bee Pollen Diets Reveal Patterns of Seasonal Foraging Resources for Honey Bees

Abstract: Western honey bees (Apis mellifera) are dominant crop pollinators, and access to summer forage is a critical factor influencing colony health in agricultural landscapes. In many temperate agricultural regions, honey bees forage extensively from non-native plants during the summer, but it is unclear whether the use of these species is due to honey bee preference for these plants or is a result of their relative abundance. The foraging choices made by native bees that have evolved with native plants can reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 53 publications
(72 reference statements)
5
44
0
Order By: Relevance
“…The average distances that we found are within the range of previous studies [36,43,71,75]. However, the decrease in distances advertised is surprising because multiple studies have indicated that honey bee colonies in the Upper Midwest and surrounding states face a dearth period when there is a lower diversity of blooming flowers at the end of the summer and into the fall (North Dakota: [76]; Ohio: [75]; Michigan: [77]; Iowa: [78]). The period from the beginning of July to early August is generally the time of year when honey bee colonies in Minnesota gain the most weight and produce the most honey [79,80].…”
Section: Discussionsupporting
confidence: 74%
“…The average distances that we found are within the range of previous studies [36,43,71,75]. However, the decrease in distances advertised is surprising because multiple studies have indicated that honey bee colonies in the Upper Midwest and surrounding states face a dearth period when there is a lower diversity of blooming flowers at the end of the summer and into the fall (North Dakota: [76]; Ohio: [75]; Michigan: [77]; Iowa: [78]). The period from the beginning of July to early August is generally the time of year when honey bee colonies in Minnesota gain the most weight and produce the most honey [79,80].…”
Section: Discussionsupporting
confidence: 74%
“…This trend is seen in the solitary bee community in the Midwest, where the summer‐flying community contains a greater proportion of dietary specialists compared to the spring‐flying community (Graenicher , Wood et al. ). Based on pollen‐foraging phenology as determined in this study, the two Michigan bumble bee species showing the greatest declines, B. affinis and B. pensylvanicus , are those that peak latest in the year.…”
Section: Discussionmentioning
confidence: 94%
“…In Michigan, the diversity of pollen types collected by the wild bee community peaks in May, before linearly declining into September (Wood et al. ). Relative to early‐emerging species, late‐emerging bumble bee species may consequently have a narrower diet simply due to a lower diversity of plants flowering at this time, necessitating greater specialization.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the crop pollinators, hardly any of the species that relied solely on semi-natural habitats were observed in large numbers. Potential reasons for this could be that non-crop pollinators may have restricted or specialised pollen diet requirements (Wood et al 2018b), or that in semi-natural habitats resource availability was too low and scattered to maintain species with larger populations for the duration of their activity period.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, more effective pollination-enhancing measures on the long term are probably permanent flower-rich linear landscape features (Morandin and Kremen 2013, Dainese et al 2017). Many of pollinator species that provide crop-pollination services collect surprising amounts of pollen from woody plants (Wood et al 2018a, Wood et al 2018b, Hass et al 2019, with up to 80% of the pollen collected from woody plants in spring (Kamper et al 2016). It may therefore be not surprising that restoration of woody elements has been shown to enhance crop pollination services (Morandin et al 2016, Dainese et al 2017), but the effects of restoration of woody elements on crop yield have not yet been studied.…”
Section: Complex Landscapes For Crop Pollination Services and Pollinamentioning
confidence: 99%